ENGLISH LANGUAGE LEARNING PROGRAM BASED ON ISLAMIC PERSONALITY VALUES FOR EARLY CHILDREN (PIAUD IAIN Kudus, 2024)
This research aims to explain the implementation of an English language learning program based on Islamic personality at Islamic playgroups in Kudus and to know the obstacles in practicing the English language based on Islamic personality. This research uses qualitative research. Techniques in collecting data are done by interviews, observation, and documentation. The result of this research is the program has been implemented according to the training curriculum at every stage. The trainers transfer their knowledge, practice English pronunciation, and give an example to the participants in using the right English language based on the Islamic personality. Then, the teachers practice the new English words based on Islamic personality in each playgroup. Through habituation, example, conditioning, and clarity of sanctions for violations of rules carried out professionally in a formal education environment based on Islamic values, children will be able to apply Islamic values in a pleasant atmosphere. The limited school time to practice pronunciation will cause children in Islamic playgroups to be less focused on practicing the English language based on Islamic personality. However, the efforts to overcome obstacles can be done with supportive non-verbal language by using thumbs up, applause, smile, handshake, and so on.